Olfaction in the Autism Spectrum. (March 2013) - Galle, Sara A; Courchesne, Valérie; Mottron, Laurent; Frasnelli, Johannes
The autism spectrum (AS) is characterised by enhanced perception in vision and audition, described by the enhanced perceptual functioning (EPF) model. This model predicts enhanced low-level (discrimination of psychophysical dimensions), and mid- and high-level (pattern detection and identification) perception. The EPF model is here tested for olfaction by investigating olfactory function in autistic and Asperger participants. Experiment 1 targeted higher-order olfactory processing by assessing olfactory identification in nine Asperger, ten autistic, and eleven typically developed individuals. Experiment 2 focused on low-level olfactory processing; we assessed odour detection thresholds and odour discrimination in five Asperger, five autistic, and five typically developed males. Olfactory identification was impaired in autistic participants relative to control and Asperger participants. Typical performance in low-level olfactory processing suggests that neural mechanisms involved in the perceptual phenotype of AS do not affect structures implicated in olfactory processing. Reduced olfactory identification is limited to autistic participants who displayed speech delay and may be due to a reduced facility to use verbal labels. The apparent absence of enhanced olfactory perception of AS participants distinguishes the olfactory system from the other sensory modalities and might be caused by the absence of an obligatory thalamic relay.